Serum Relmβ combined with abdominal signs may predict surgical timing in neonates with NEC: A cohort study - Liu, Xiao-Chen; Guo, Lu; Ling, Ke-Ran; Hu, Xiao-Yu; Shen, Yu-Jie; Li, Lu-Quan (Frontiers in Pediatrics, 2022)
Aims To examine the predictive value of serum biomarkers combined with other indicators for necrotizing enterocolitis (NEC) surgery decision-making. Methods Clinical data, including baseline information, clinical features, imaging presentation and serum assessment, of the infants enrolled were collected, and the serum concentrations of HBD2, HMGB-1, Claudin-3 and Relmβ were determined. Student’s t test, the Mann–Whitney U test, the chi-square test and logistic regression analysis were used. Receiver operating characteristic (ROC) curves were also generated. Results Forty-nine infants were enrolled, with twenty-three in the surgical NEC group and twenty-six in the medical NEC group. There were no differences in the baseline clinical information, including birth weight, gestational age, admission age and risk factors, during pregnancy and before enrollment (P>0.05). Peritonitis, intestinal adhesion and sepsis were more common in the surgical group (P<0. 05). The incidences of abdominal distention, abdominal wall tenseness, abdominal tenderness and absent bowel sounds in the surgical group were significantly higher when NEC occurred (P<0.05). There were no differences between the two groups in the imaging presentation (P>0.05). The concentration of Relmβ [(8.66 (4.29, 19.28) vs. 20.65 (9.51, 44.65)] in the surgical group was significantly higher (P<0.05). Abdominal wall tenseness, abdominal tenderness and a Relmβ concentration >19.7 μmol/L were included in the predictive model, and the AUC of the predictive score was 0.943 (95% CI: 0.891~1.000) (P<0.05). Conclusion Serum Relmβ concentration combined with abdominal wall tenseness and abdominal tenderness may be useful in determining surgical timing in neonates with NEC.